2017
DOI: 10.5194/wes-2-285-2017
|View full text |Cite
|
Sign up to set email alerts
|

Why the Coriolis force turns a wind farm wake clockwise in the Northern Hemisphere

Abstract: Abstract.The interaction between the Coriolis force and a wind farm wake is investigated by Reynoldsaveraged Navier-Stokes simulations, using two different wind farm representations: a high roughness and 5 × 5 actuator disks. Surprisingly, the calculated wind farm wake deflection is the opposite in the two simulations. A momentum balance in the cross flow direction shows that the interaction between the Coriolis force and the 5 × 5 actuator disks is complex due to turbulent mixing of veered momentum from above… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…One of the studies was performed with LES using a precursor simulation [16], this study indicated that a turn to the left dominated. These results gave a different conclusion than was found by Van der Laan [15]. Other studies found that the inclusion of the Coriolis force had some impact on the production for a full wake direction due to the turn of the wake [17].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…One of the studies was performed with LES using a precursor simulation [16], this study indicated that a turn to the left dominated. These results gave a different conclusion than was found by Van der Laan [15]. Other studies found that the inclusion of the Coriolis force had some impact on the production for a full wake direction due to the turn of the wake [17].…”
Section: Introductionmentioning
confidence: 75%
“…Here Ω is the rotation of the Earth, φ is the latitude, u, w are the instantaneous local velocities and U, W are the mean values used in the FBL. The latitude 43.3 degrees is used in the studied case which corresponds to the Coriolis parameter f = 10 −4 1 s , also used by Van der Laan [15]).…”
Section: The Coriolis Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alya is an HPC code developed at the Barcelona Supercomputing Centre (BSC) to run large-scale applications. The code was recently tested on 100 000 processors and showed a parallel efficiency above 90 % (Vázquez et al, 2016). The k-ε model has been implemented and used in Alya for the present work.…”
Section: Model Descriptionmentioning
confidence: 99%